2019
DOI: 10.1016/j.cell.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Viral Capsid Trafficking along Treadmilling Tubulin Filaments in Bacteria

Abstract: Highlights d Capsids traffic along a viral encoded tubulin filament d Treadmilling of the filament provides the mechanism of capsid movement through the cell d Rotation of phage nucleus by the filament distributes capsids for efficient DNA packaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(149 citation statements)
references
References 34 publications
4
145
0
Order By: Relevance
“…Fluorescence recovery after photobleaching (FRAP) demonstrated that normal PhuZ spindles treadmill (Fig. 3b , left; 16 ), while the hybrid spindles were not dynamic (Fig. 3b , right).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence recovery after photobleaching (FRAP) demonstrated that normal PhuZ spindles treadmill (Fig. 3b , left; 16 ), while the hybrid spindles were not dynamic (Fig. 3b , right).…”
Section: Resultsmentioning
confidence: 99%
“…These viruses encode a distant homologue of the eukaryotic tubulin that localizes this nucleus-like structure in the middle of the virocell (i.e. the virus-infected cell) and treadmills toward it the viral capsids that were assembled on the membrane 26 . It is possible that viractins play a similar role during viral infections by controlling the localization of the viral factory close to the host nucleus (e.g., as seen in Yasminevirus 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 55 ). The filament-forming phage tubulin PhuZ ( 56 ) and its roles in the spatial organization of large phage DNA and directed movements of capsids in the cells have been demonstrated ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%